Asthma in children with sickle cell disease. Issue 3 (June 2019) - Willen, Shaina M.; Rodeghier, Mark; DeBaun, Michael R.
Abstract : Purpose of review: Asthma is common in children with sickle cell disease (SCD) and appears to be associated with increased morbidity. Providers caring for children with SCD have struggled with the question of whether asthma exists as a true comorbidity or whether certain aspects of the chronic inflammatory disease gives children with SCD an asthma-like phenotype. Recent findings: Clinical signs and symptoms seen in children with asthma in the general population, such as wheezing, airway hyperresponsiveness, atopy, elevated leukotrienes, and abnormal lung function are seen in children with SCD both with and without a diagnosis of asthma. Summary: Current evidence highlights that the presence of lung disease in children with SCD has significant implications irrespective of the underlying cause, including asthma. Further research should focus on well tolerated and effective interventions to prevent disease-related complications for children with pulmonary complications of SCD.